The hydraulic performance of the storm chamber in a new manhole designed for separate sewer systems. Issue 6 (9th November 2020) - Abbas, Alaa; Carnacina, Iacopo; Ruddock, Felicity; Alkhaddar, Rafid; Rothwell, Glynn; Andoh, Robert
Abstract : This paper presents the hydraulic study of a new manhole geometry, designed to allow the installation of separate sewer systems in narrow streets. The new manhole design comprises two chambers in one structure to manage separate flows. The new shape of the manhole generates a new flow pattern for stormwater. It is therefore important to understand the hydraulic properties of sewer systems using the newly designed stormwater manhole chamber. The present study focuses on exploring the hydraulic performance of the storm chamber, which is usually characterized by significant head losses and shockwaves, these related to different flow regimes. A physical model was used to carry out a systematic experiment to explore the flow characteristics of the manhole under both subcritical and transitional flow conditions. The results revealed an enhancement in head loss with higher amplitude waves generated at transition flow when compared with a conventional manhole.